A Parkinson's disease CircRNAs Resource reveals a link between circSLC8A1 and oxidative stress. Issue 11 (6th November 2020) - Hanan, Mor; Simchovitz, Alon; Yayon, Nadav; Vaknine, Shani; Cohen‐Fultheim, Roni; Karmon, Miriam; Madrer, Nimrod; Rohrlich, Talia Miriam; Maman, Moria; Bennett, Estelle R; Greenberg, David S; Meshorer, Eran; et al.
Abstract :